The impact of HIV diagnosis on pregnancy or post birth and its effects on women’s life: integrativeliterature review (Research, Society and Development, 2021)
Objective: To synthesize the knowledgeproduced in the scientificliterature in the lastfiveyears, about the impact of the diagnosis of the HumanImmunodeficiencyVirus (HIV) in pregnancy or postpartum and its effects on the lives of women.Methodology: This is an integrativeliterature review of a qualitativenature, with primarystudiespublished in the time frame from 2015 to 2020, in Portuguese and English, in the MedLine, Lilacs and BDEnfdatabasesthrough the Virtual Health Library (VHL), and PubMed, usingsearch strategies, according to the specificities of the databases in question. Results: 11 primarystudieswereselected, from which the following categorieswereextracted: 1) Feelings of women when receiving the diagnosis of HIV during pregnancy or postpartum; 2) Implications of disclosing the diagnosis to the partner, familymembers and others. 3) Motherhood and HIV, the mainchallengesfaced by mothers after diagnosis. 4) The role of health professionals in assisting pregnant women and women who have recentlybeen diagnosed with HIV. Conclusion: This literature review reinforces the need for more studies that address the implications of HIV discovery during pregnancy or postpartum and that enable health professionals to understandaboutthese implications so that strategies can be devised to minimize them. It is hoped that this study may arouseinterest in the topicaddressed, so that work and also actions that can contribute to the promotion of the health of women diagnosed with HIV in Basic Health Units (UBSs) or maternityunitsthrough interventions based on interventions are developed. in the demandsfound with the use of strategies that meet the individual needs of eachwoman, that promote quality of life and enable the re-signification of life after HIV diagnosis.